Frequency of New Onset Diabetes Mellitus in Patients with Live Related Renal Transplant - Rameez Chandio, Raza Muhammad Jamro, Muhammad Shoaib, Sajid Iqbal, Ijaz Ur Rehman, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Kidney transplant is only the cure of end stage renal diseases. It is because it provides the maximum replacement of renal functions. New onset diabetes after transplantation is one of the serious and chronic problem of renal transplant. NODAT is reported to occur in 4%-25% of renal transplant recipients. New onset diabetes may be identified after the renal transplant at any time. Objective: The study aimed to determine the frequency of new onset of diabetes mellitus in the patients with live related renal transplant. Study design: It is a retrospective study conducted in the department of nephrology and transplantation, Pir Abdul Qadir Shah Jeelani Institute of Medical Sciences, Gambat for the duration of six months from July 2022 to December 2022. Material and Methods: There were 50 patients in PTDM group and 70 were in the non PTDM group. The anthropometric and clinical characteristics were recorded. The SPSS software was used for the analysis. The Patients were divided into two groups according to the diagnosis. Results: The average age of patients in PTDM group is 43.2 years whereas in non-PTDM group the average age is 45 years. Statistical analysis revealed that results are statistically significant with 95% CI. Most of the cases appeared during 2 weeks of transplant however, 14 patients also reported about diabetes after 2 months of transplant. Conclusion: Common metabolic disease PTDM is usually diagnosed during first 6 weeks of renal transplantation. Old age, family history of diabetes, the presence of IGF during first week of transplantation are some of the risk factors that lead to PTDM prevalence. The PTDM was observed in the 40% patients in our study. Keywords: renal functions and post-transplant diabetes mellitus.